Analisis Penerapan Pajak Pertambahan Nilai pada PT. Quantum Mandiri International - Marini Gunardhy; Barlia Annis Syahzuni (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The research was conducted using a mixed method between quantitative and qualitative to determine the relationship between inflation and Value Added Tax (VAT). In addition, this research was also conducted to find out how the application of VAT in terms of calculation, payment and reporting stated in the company's Periodic Notification Letter (PNL). This is done to avoid tax sanctions, one of which is the receipt of a Tax Collection Letter (TCL). The independent variable uses inflation and the dependent variable uses VAT. This study uses data on inflation and VAT reported as much as 36 data with the period 2021-2023. Simple linear regression analysis is used in the data processing method and processed using statistical data processing tools. The results of existing data processing show that inflation has a positive impact on VAT.  In the February 2021 and March 2021 VAT Periodic Tax Returns there are still corrections caused by errors in making Tax Invoices (TI), resulting in delays in payment and reporting of VAT NPL. Due to this delay, it resulted in the receipt of STP from the Tax Service Office (TSO) and a response has been made by the company to the TCL that has been received. For the April 2021 to December 2023 VAT NPL, the company has paid and reported VAT so that no TCL has been received from the TSO.